Identification and implications of the London Clay Formation divisions from an engineering perspective. Issue 5 (October 2020) - Standing, J.R.
Abstract: Historically, engineers frequently viewed the London Clay Formation (LC) as uniform, homogeneous and rather uninteresting. Chris King's seminal work provided a much deeper insight into the characteristics of the LC and how it can be split into divisions, based on the depositional history of the formation and the microfauna present. LC water content profiles were compiled from continuous cores as part of an investigation into variations in tunnelling-induced settlements across St James's Park, allowing distinct zones to be identified. These were found to coincide exactly with the divisions identified by Chris King almost twenty years earlier. Water content profiles can be developed as part of a ground investigation and used to help establish the boundaries between King's divisions. Based on two further water content profiles from Hyde Park and St John's Wood a new methodology for locating the boundaries of the divisions, involving a trend-line for sub-Division A3, is proposed and tested, relevant to conditions in central London. In developing the method, significant differences in the elevation of the divisions between the three sites is observed, suggesting geological processes such as folding or faulting have influenced the LC along the ∼5-km length of the section. Once the boundaries of the LC divisions are known, geotechnical engineers have a greatly improved overall understanding of the ground conditions and how the ground will respond to engineering works such as tunnelling and deep excavations. Broad engineering implications of the divisions are described and discussed, citing case histories where possible.